Associations between social determinants of health and mental health disorders among U.S. population: a cross-sectional study - S. Tanarsuwongkul; J. Liu; M. Spaulding; K. Perea-Schmittle; M. Lohman; Q. Wang (Epidemiology and Psychiatric Sciences)
Abstract Aims The impact of social determinants of health (SDOH) on mental health is increasingly realized. A comprehensive study examining the associations of SDOH with mental health disorders has yet to be accomplished. This study evaluated the associations between five domains of SDOH and the SDOH summary score and mental health disorders in the United States.